Systemic therapy of psoriasis and psoriatic arthritis: assignment algorithms - Marianna M. Khobeysh; Evgeny V. Sokolovskiy (Vestnik Dermatologii i Venerologii)
The article contains a review of modern literature data and the authors’ personal long-term experience in treating patients with psoriasis and psoriatic arthritis. The possibilities of prescribing various drugs for systemic therapy based on the clinical situation, issues of monitoring and evaluating the effectiveness of therapy, and the mechanism for switching therapy from one pharmacological medication to another are discussed in detail. Therapy of patients with psoriasis requires solving the complex issue of drug selection, which depends on many factors. The choice of systemic therapy algorithm is an important issue that determines the effectiveness and safety of treatment, influences the prognosis of the disease and the patient’s quality of life.